Use of Geography Education in Local Governments - (:unkn) unknown (MARMARA UNIV, 2016)
This study is carried out in order to identify the effects of geography education and the status and influence of geography graduates have in local governments. Accordingly, the study group of this study is composed of district municipalities of Istanbul with whom the interviews are held. The method used in the study is qualitative and the pattern is phenomenology, since the questions needed to be answered are Why?, How? and In what way?. A half-configured interview form is used in order to assess the effect of geography education in district municipalities. Face to face interviews are held with persons in the relative units of municipalities. In the study, several categories are created to identify the effects of geography education. Information is attempted to be gathered using open-ended questions, for which the answers are given voluntarily and evaluated independently, and views of 10 different district municipalities are taken into consideration. Using the information, it is appraised that in some municipalities, geography graduates are employed and the views of these geographers can be taken into consideration in the projects that are being carried out. In the meantime, it is appraised that not enough geography graduates are employed in local governments and the ones who are employed are not very effective. The most important factor in this is the lack of a permanent staff and a job description as geographer. Because the appointments are done according to staff in the public service, geography graduates cannot find jobs. As a result, geography education does not have enough effect in the services and projects of municipalities.
Keywords: Geography; geography education; local governments; project